Up‐regulation of cell division cycle 20 expression alters the morphology of neuronal dendritic spines in the nucleus accumbens by promoting FMRP ubiquitination. Issue 2 (19th June 2022) - Wang, Xin; Li, Fei; Zhu, Jun; Feng, Dayun; Shi, Yingwu; Qu, Liang; Li, Yang; Guo, Kang; Zhang, Yue; Wang, Qiang; Wang, Naigeng; Wang, Xuelian; et al.
Abstract: The nucleus accumbens (NAc) is the key area of the reward circuit, but its heterogeneity has been poorly studied. Using single‐cell RNA sequencing, we revealed a subcluster of GABAergic neurons characterized by cell division cycle 20 (Cdc20) mRNA expression in the NAc of adult rats. We studied the coexpression of Cdc20 and Gad1 mRNA in the NAc neurons of adult rats and assessed Cdc20 protein expression in the NAc during rat development. Moreover, we microinjected AAV2/9‐hSyn‐Cdc20 with or without the dual‐AAV system into the bilateral NAc for sparse labeling to observe changes in the synaptic morphology of mature neurons and assessed rat behaviors in open field and elevated plus maze tests. Furthermore, we performed the experiments with a Cdc20 inhibitor, Cdc20 over‐expression AAV vector, and Cdc20 conditional knockout primary striatal neurons to understand the ubiquitination‐dependent degradation of fragile X mental retardation protein (FMRP) in vitro and in vivo. We confirmed the mRNA expression of Cdc20 in the NAc GABAergic neurons of adult rats, and its protein level was decreased significantly 3 weeks post‐birth. Up‐regulated Cdc20 expression in the bilateral NAc decreased the dendritic spine density in mature neurons and induced anxiety‐like behavior in rats. Cdc20‐APC triggered FMRP degradation through K48‐linked polyubiquitination in Neuro‐2a cells and primary striatal neurons and down‐regulated FMRP expression in the NAc of adult rats. These data revealed that up‐regulation of Cdc20 in the bilateral NAc reduced dendritic spine density and led to anxiety‐like behaviors, possibly by enhancing FMRP degradation via K48‐linked polyubiquitination. Abstract : Cell division cycle 20 (Cdc20) mRNA serves as a marker of a GABAergic neuronal subpopulation in the nucleus accumbens (NAc). Up‐regulation of Cdc20 expression in mature medium spiny neurons (MSNs) by transfection with AAV‐hSyn‐Cdc20 reduces the density of dendritic spines in the bilateral NAc. This effect is possibly achieved by the enhancement of K48‐linked polyubiquitination and degradation of FMRP through the Cdc20‐APC pathway, and this process can be blocked by the Cdc20 inhibitor apcin. In further research, Cdc20 may be a desirable therapeutic target for modulating the morphology of dendritic spines and abnormal behaviors.